Modified International Toastmaster Approach to Improve Public Speaking Competence - Rita Hartati; Meisuri; Siti Aisyah Ginting (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2022)
Competency Based Education is very much needed in the era of the industrial revolution 5.0 and the determination of Toba Caldera as a UNESCO Global Geopark provides opportunities, encourages economic and sustainable development, requires skilled worker who has various competencies in a field of work. This competency improvement is also the outcomes of Independent Learning-Independent Campus. This research was the type of online survey tools associative research conducted factual information to obtain the truth. Online Survey Tools Research generally uses a google form as questionnaire instrument filled out by participants used certain methods. (Vasanta Raju 2018). Modified International Toastmaster model, testing and evaluating the model created by the Public Speaking training program involving 30 students of the English Literature Department Universitas Negeri Medan. The findings related to competence using the 10 Toastmaster International project speech delivery have shown at the pie chart (see figure 3.1 to 3.10). Modified International Toastmaster is associated with the six tasks models of Indonesian National Qualification Framework called KKNI to maximize the improvement of various competence in public speaking.